Injection-induced slip heterogeneity on faults in shale reservoirs - Jia, Yunzhong (2022)
Managing fluid stimulation protocols is an effective means to mitigate the risk of injection-induced earthquakes during shale gas development. The success of these protocols is dependent on our understanding of fluid pressure heterogeneity and the associated inhomogeneous slip on critically stressed faults. Here we show the evolution of velocity-weakening zone on a simulated fault, derived from fluid injection and velocity stepped experiments, and the corresponding non-uniform fluid pressure distribution, recovered from coupled hydro-mechanical simulations. Our results indicate that the sharp extension of velocity-weakening zone occurs before the nucleation of fault rupture, which could be an indicator to avoid the reactivation of other fault patches beyond the stimulated zone. The dynamic rupture is estimated to extend much faster than the maximum speed of the velocity-weakening zone front. We infer that the velocity-weakening zone may further expand and fully control the fault behavior after multiple slip events.